RESILIENSI ANAK JALANAN DI KECAMATAN MANDONGA KOTA KENDARI - Wibowo, Nur Suci Ariyanti; Arsyad, Muhammad; Yusuf, Bakri (Universitas Halu Oleo, 2020)
This research uses descriptive qualitative research with data collection techniques, namely observation, interviews and document study. The results showed that: the formation of street child resilience in Mandongan District, Kendari City consists of several reasons, including street children in Mandonga District who have strong emotional regulation, optimism which indicates that they have self-confidence, individual ability to identify problems, have a great sense of empathy. and self-efficacy which represents a belief. The factors that influence the resilience of street children in Mandonga District, Kendari City are the presence of institutions such as the Social Service and students and the surrounding community who always provide support and motivation as well as guidance through social activities both individually and in groups